A battle for access to the streets of a "World-Class African City": Assessing the challenges facing the City of Johannesburg in the management of street trading in the inner-city - Zulu, Nompumelelo (University of Cape Town, 2020)
The paper identifies the main challenges faced by the City of Johannesburg in the management of street trading in Johannesburg's inner-city. Street trading is very important as it constitutes a great proportion of the informal sector in South Africa, and it plays a great role in the alleviation of poverty and unemployment. Government acknowledges the significance of street trading but this does not translate into urban policy and practice. There is a need for government to be more supportive and developmental in the management of street trading in urban governance. The paper found that the 2013 Constitutional Court Judgement on Operation Clean Sweep has brought about a shift in the City of Johannesburg's approach and attitude towards street trading, however, key challenges remain. Firstly, the City of Johannesburg needs to establish a holistic, developmental and collaborative management model for street trading as the current one is fragmented and inconsistent. The mismanagement of street trading has left traders vulnerable to police harassment and corruption, and it has resulted in the "crime and grime" the City of Johannesburg so often blames street trading for. Secondly, the City of Johannesburg needs to balance its desire to attain world-class African city status with the needs of the poor and marginalized - economic development, urban renewal and investment should not take place at the expense of the poor. Thirdly, street traders need to be at the center of the management model, currently business and private interests are at the center of the model. Lastly, the City of Johannesburg needs to be more creative and lenient in accommodating the growing number of street traders in the inner-city. The City of Johannesburg needs to stop criminalizing street trading through the creation of scarcity. The findings of this paper have implications for urban management policy and practice. Research was conducted through interviews with the Department of Economic Development officials responsible for street trading; draft policy and government documents were used; and secondary sources were drawn upon.